Comparing the effectiveness of water-based exercises and Yoga on memory and dynamic balance of elder people - khadijeh Irandoust; Morteza Taheri; Ali Seghatoleslami (University of Tehran, 2015)
The purpose of this study is to investigate the effect of physical activity onmemory and dynamic balance of elder people. Subjects (n=15) were selected asvolunteers. The intervention was performed in an eighteen session period, threetimes a week (each session, 45 minutes). Yoga training was performed for mentalrelaxation. Wexler test was performed for memory evaluation. Seat up test wasused to test the dynamic balance. The results suggested that water-based exercisesand Yoga protocol have had a positive significant effect on memory (p=0.03) anddynamic balance. It was concluded that a selected physical activity program,especially water-based exercises has less potential for making people injured.